2013
DOI: 10.1002/ajpa.22420
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic examination of links between diet, social differentiation, and DISH at the post‐medieval Carmelite Friary of Aalst, Belgium

Abstract: Stable isotope ratios (δ(13) C and δ(15) N) were measured in human burials from the post-medieval (16th-18th c. AD) Carmelite friary burial grounds at Aalst, a town in Flanders, Belgium. Dietary patterns of 39 adult individuals were analyzed, from a mixed monastic and lay population buried in three different locations, reflecting groups with differing social status. The data show significant variation in the consumption of perhaps meat, but certainly also marine protein between females and males. This result r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 60 publications
3
50
0
8
Order By: Relevance
“…Isotopic analyses are widely used to unravel dietary differences between social status in late medieval and early modern times in several European regions (Polet and Katzenberg 2003;Richards 2005, 2007;Fornaciari 2008, Kjellström et al 2009Mundee 2010;Yoder 2012;Lubritto et al 2013;Quintelier et al 2014;Lamb et al 2014;Alexander et al 2015;Olsen et al 2016, van der Sluis et al 2016. In France, the diet of urban poor individuals was documented (Bocherens 1991;Herrscher et al 2001Herrscher et al , 2003Herrscher et al , 2004, but differences between socio-economic groups have yet to be investigated.…”
Section: Introduction Stable Isotope Studies Of Late Medieval and Earmentioning
confidence: 99%
“…Isotopic analyses are widely used to unravel dietary differences between social status in late medieval and early modern times in several European regions (Polet and Katzenberg 2003;Richards 2005, 2007;Fornaciari 2008, Kjellström et al 2009Mundee 2010;Yoder 2012;Lubritto et al 2013;Quintelier et al 2014;Lamb et al 2014;Alexander et al 2015;Olsen et al 2016, van der Sluis et al 2016. In France, the diet of urban poor individuals was documented (Bocherens 1991;Herrscher et al 2001Herrscher et al , 2003Herrscher et al , 2004, but differences between socio-economic groups have yet to be investigated.…”
Section: Introduction Stable Isotope Studies Of Late Medieval and Earmentioning
confidence: 99%
“…The proposal that inter-population differences and variation in the anatomy of the dimorphism of the skeletal structure in humans has not yet been performed. Also, Quintelier et al (2014) demonstrated, based on isotopic evidence, that males from post-Medieval Belgium (16th-18th century) probably had a higher intake of animal protein (meat and fish). A difference in meat consumption could potentially contribute to the differences in the shape and size (or just one of these) of male versus female mandibles, since the differences in structure between foods, or even between processed and un-processed foods, can have an impact on the muscle activity needed for chewing (Zink and Lieberman, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon and nitrogen stable isotope compositions were measured as the ratios of the heavier isotopes to the lighter isotopes 15 N) data for fish and terrestrial domestic mammals from archaeological sites in the Scheldt Basin, Belgium (after Fuller et al 2012;Quintelier et al 2014). Marine fish included sturgeon, shad, plaice, flounder, flatfish, halibut, herring, haddock, whiting, and cod; freshwater fish included roach, ide, tench, carp, pike, and cyprinids.…”
Section: Methodsmentioning
confidence: 99%